Effects of ranitidine and nizatidine on the risk of gastrointestinal cancer - Kang, Hyejung; Nam, Chung Mo; Choi, Dong-Woo; Park, Sohee (Frontiers in Oncology, 2023)
Purpose: Gastrointestinal (GI) cancer occurs in digestive organs such as the stomach, colon, liver, esophagus, and pancreas. About 83,034 cases occurred in Korea alone in 2020. Dietary factors, alcohol consumption, Helicobacter pylori, and lifestyle factors increase the incidence of diseases such as gastritis, peptic ulcer, pancreatitis, and gastroesophageal reflux disease, which can develop into GI cancer. However, in 2019, the US Food and Drug Administration announced that the drugs ranitidine and nizatidine, which are used for digestive disorders, contain carcinogens. In this study, we investigated the effects of ranitidine and nizatidine on the development of GI cancer. Materials and methods: In this study, using National Health Insurance Service–National Sample Cohort, subjects who developed GI cancer were enrolled in the case group, and those who were at risk of, but did not develop, cancer were enrolled in the control group. Thereafter, risk-set matching was performed (1:3 ratio) by sex and age at the time of diagnosis of cancer in the case group. Through this procedure, 22,931 cases and 68,793 controls were identified. The associations of ranitidine and/or nizatidine with GI cancer were confirmed by adjusted odds ratios (aORs) and 95% confidence intervals (CIs) calculated through conditional logistic regression analysis. Results: The aORs of ranitidine and/or nizatidine users were lower than those of nonusers in all average prescription days groups (< 30 days/year: aOR [95% CI] = 0.79 [0.75-0.82]; 30–59 days/year: aOR [95% CI] = 0.66 [0.59-0.73]; 60–89 days/year: aOR [95% CI] = 0.69 [0.59-0.81]; ≥ 90 days/year: aOR [95% CI] = 0.69 [0.59-0.79]). Sensitivity analyses were conducted with different lag periods for the onset of GI cancer after drug administration, and these analyses yielded consistent results. Conclusion: Our study, using nationwide retrospective cohort data, did not find evidence suggesting that ranitidine and nizatidine increase the risk of GI cancer. In fact, we observed that the incidence of GI cancer was lower in individuals who used the drugs compared to nonusers. These findings suggest a potential beneficial effect of these drugs on cancer risk, likely attributed to their ability to improve digestive function.